Feedback from American participants of a Mental Health First Aid training course. Issue 2 (15th June 2015) - Ploper, Viviana; Jones, Rise; Kraus, Dana J; Schmidt, Annie; Corrigan, Patrick
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Mental Health First Aid (MHFA) is a course meant to train participants in how to identify and respond to signs of mental disorders and crises. The purpose of this paper is to conduct a qualitative study of MHFA participants to get a sense of some values and challenges associated with the training. Design/methodology/approach – Results from an online survey of 143 participants yielded 24 discrete themes. Survey responses were gathered into a single data set and coded by two independent raters. Findings – Themes were sorted into four categories: MHFA benefits, training limitations, challenges to MHFA, and resources that facilitate MHFA. Several benefits emerged, consistent with findings from Australian studies. Research limitations/implications – Findings represent a sample of people who completed the program in Chicago; research needs to determine how perceived benefits and limitations vary by geographic area. Originality/value – Findings echoed many of the benefits found in studies conducted outside the USA and can be used to further improve MHFA training as it expands in the US market.